Pola Penggunaan Produk Over The Counter (OTC) pada Mahasiswa Fakultas Kedokteran yang Menderita Akne Vulgaris - Regina Regina; Inneke Jane Hidajat; Franklind Matthew; Melyawati Melyawati (Bahasa Indonesia, 2022)
Introduction: Acne vulgaris (AV) is a skin disorder caused by inflammation in the pilosebaceous unit and may cause a psychosocial burden for patients. Self-medication is common in medical students, including in treating AV. This study aimed to determine the behavioral characteristics of using over-the-counter (OTC) products for acne-prone skin in medical students in Jakarta. Methods: This was a cross-sectional observational study of 100 medical students with AV. The study was conducted using questionnaires consisting of clinical survey, medications, and OTC products. The clinical assessment of the severity of AV was determined using the Global Acne Grading System (GAGS) criteria. Results: Sixty-nine study subjects only used OTC products for their acne management. The most common OTC product was a facial cleanser, which facial cleanser (89 subjects) and cleansing oil (29 subjects). Fifty percent of the study subjects did not know the active ingredients in the products; 15% used benzoyl peroxide, 13% used topical retinoid, and 12% used nicotinamide. Conclusion: Self-medication with OTC products for acne-prone skin is frequent among medical students in Jakarta, and the most commonly used product is a facial cleanser. Most study subjects did not know the active ingredients in their OTC products.